Superabsorbent sodium carboxymethyl cellulose membranes based on a new cross-linker combination for female sanitary napkin applications. (15th November 2020) - G, Reshma; C.R, Reshmi; Nair, Shantikumar V.; Menon, Deepthy
Highlights: STMP & AlS cross-linker combination offered good matrix integrity after sorption for NaCMC/St-LY& NaCMC-PI membranes. Sorption characteristics of both NaCMC/St-LY and NaCMC-PI membranes proved their utility for female hygiene applications. NaCMC/St-LY possessed good superabsorbent characteristics with high water retention capacity. NaCMC/St-LY showed high soil degradability, implying its biodegradability. Abstract: The main intent of this investigation was to retain the strength and superabsorbency of natural and non-toxic biodegradable polymers using an innovative combination of cross-linkers for application as the absorbent core of sanitary napkins. For this, sodium carboxymethyl cellulose (NaCMC) and starch were blend to form membranes by phase inversion and lyophilisation, using an optimized cross-linker combination of sodium trimetaphosphate (STMP) and aluminium sulphate (AlS). Optimal cross-linking of NaCMC and starch hampered membrane dissolution and disintegration, yielding a microtextured surface morphology. The membranes were biodegradable and yet possessed the requisite flexibility and mechanical strength for the proposed application, without compromise of superabsorbency. Lyophilised membranes possessed higher immediate water and blood sorption with ∼50% water retention capabilities when compared to the phase inversion technology. The results suggest that the developed membranes can be a cost-effective degradable alternative to the commercial polyacrylate-based nonbiodegradable sanitary products.